A thermodynamically stable layered double hydroxide heterostructure - Ragavan, A; Williams, G; O'Hare, D (2009)
A novel heterostructure was synthesised via the intercalation of 4-nitrophenolate (4-NP) into [LiAl2(OH)6]Cl·xH 2O ([Li-Al-Cl]). Its interlayer spaces are alternatively occupied by 4-NP and chloride ions. The intercalate is structurally analogous to staging intermediates reported previously. However, data obtained from time-resolved in situ energy-dispersive X-ray powder diffraction clearly differentiate it from a reaction intermediate. The [Li-Al-Cl-4-NP] heterostructure is formed as a thermodynamically stable product when [Li-Al-Cl] is treated with a small excess of 4-NP over an extended period of time at elevated temperatures (above 70 °C). The heterostructural compound exhibits selective anion exchange when reacted with a range of organic and inorganic anions. © 2009 The Royal Society of Chemistry.